Leucine-Rich Repeat Kinase 2 Is Associated With Activation of the Paraventricular Nucleus of the Hypothalamus and Stress-Related Gastrointestinal Dysmotility - Maekawa, Tatsunori; Tsushima, Hiromichi; Kawakami, Fumitaka; Kawashima, Rei; Kodo, Masaru; Imai, Motoki; Ichikawa, Takafumi (Frontiers in Neuroscience, 2019)
Leucine-rich repeat kinase 2 (LRRK2) is a molecule associated with familial and sporadic Parkinson’s disease. It regulates many central neuronal functions such as cell proliferation, apoptosis, autophagy, and axonal extension. Recently, it has been revealed that LRRK2 is related to anxiety/depression-like behavior, implying an association between LRRK2 and stress. In the present study, we investigated for the first time the stress pathway and its relationship to gastrointestinal motility in LRRK2-knockout (KO) mice. The mice were subjected to acute restraint stress, and analyzed for activation of the paraventricular nucleus of the hypothalamus (PVN) using an immunohistochemical approach. Phosphorylation of extracellular signal-regulated kinase 1/2 (ERK1/2) was assessed by Western blotting. The KO mice showed a lower number of c-Fos-positive cells and disruption of the ERK signaling pathway in the PVN in the presence of restraint stress. Stress responses in terms of both upper and lower gastrointestinal motility were alleviated in the mice, accompanied by lower c-Fos immunoreactivity in enteric excitatory neurons. Our present findings suggest that LRRK2 is a newly recognized molecule regulating the stress pathway in the PVN, playing a role in stress-related gastrointestinal dysmotility.